2019
DOI: 10.1002/ece3.4870
|View full text |Cite
|
Sign up to set email alerts
|

Limited effects of early snowmelt on plants, decomposers, and soil nutrients in Arctic tundra soils

Abstract: In addition to warming temperatures, Arctic ecosystems are responding to climate change with earlier snowmelt and soil thaw. Earlier snowmelt has been examined infrequently in field experiments, and we lack a comprehensive look at belowground responses of the soil biogeochemical system that includes plant roots, decomposers, and soil nutrients. We experimentally advanced the timing of snowmelt in factorial combination with an open‐top chamber warming treatment over a 3‐year period and evaluated the responses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 99 publications
4
17
0
Order By: Relevance
“…6 ), while mass losses from deployed conifer needles were similar across the full 700-meter gradient ( Table S2 ). This was surprising considering the differences in snowmelt timing across elevation ( Table S1 ); however, these results agree with other studies that have shown minimal impact on microbial structure with no lasting effects on microbial biomass and nutrient cycling processes after experimental snowmelt manipulations ( Conner, Gill & Harvey, 2017 ; Darrouzet-Nardi et al, 2019 ). A plausible explanation is that ecological resilience overcomes the effects of accelerated snowmelt without additional climate variables of higher temperatures and lower precipitation ( Darrouzet-Nardi et al, 2019 ).…”
Section: Discussionsupporting
confidence: 86%
“…6 ), while mass losses from deployed conifer needles were similar across the full 700-meter gradient ( Table S2 ). This was surprising considering the differences in snowmelt timing across elevation ( Table S1 ); however, these results agree with other studies that have shown minimal impact on microbial structure with no lasting effects on microbial biomass and nutrient cycling processes after experimental snowmelt manipulations ( Conner, Gill & Harvey, 2017 ; Darrouzet-Nardi et al, 2019 ). A plausible explanation is that ecological resilience overcomes the effects of accelerated snowmelt without additional climate variables of higher temperatures and lower precipitation ( Darrouzet-Nardi et al, 2019 ).…”
Section: Discussionsupporting
confidence: 86%
“…All model input data sets were reprojected into a 1 km resolution Albers projection and resampled to an 8 d time step consistent with the model simulations. Other ancillary data sets included the 30 m National Land Cover Database (NLCD) 2011 (Jin et al, 2013), 50 m SOC estimates for Alaska (to 1 m depth; Mishra et al, 2017), and the global 9 km mineral soil texture data developed for the SMAP L4SM algorithm (De Lannoy et al, 2014). The dominant NLCD land cover type within each 1 km pixel was used to define the modeling domain, with open water and perennial ice and snow areas excluded (Fig.…”
Section: Model Inputs and Parameterizationmentioning
confidence: 99%
“…Indeed, an increased frequency and severity of freeze-thaw cycles in soil due to reduced snow cover during the winter months could impact microbial and biogeochemical cycles during snowmelt, regardless of its timing. Any or all of these winter and spring climate change impacts could potentially lead to cross-season legacy effects [23,24]. Earlier spring snowmelt, in particular, could disrupt the temporal dynamics of plant and soil microbial resource demands [16,25], with potential consequences for ecosystem C and N retention in these widespread and vulnerable mountain ecosystems [26].…”
Section: Introductionmentioning
confidence: 99%